Larval morphology of Aphodius sus (Herbst) and A. variicolor Koshantschikov (Coleoptera: Scarabaeidae: Aphodiinae) - Frolov, Andrey V. (Zootaxa, 2009)
Morphological descriptions and illustrations are presented for third-instar larvae of two species of the scarab beetle genus Aphodius Illiger: Aphodius (Heptaulacus) sus (Herbst) and A. (Chilothorax) variicolor Koshantschikov. These descriptions are based on material collected in European Russia. Larvae were collected from the soil with no association to dung although the adults of the same species normally occur in horse dung. Characters of the larvae are compared with those of described larvae of other species.